Optimizing Marketing Efficiency and Farmer's Share in the Oil Palm Industry: A Study of Marketing Channels and Margins in Pasar VII Namo Terasi Village, Sei Bingai District, Langkat Regency - Helova Leonard Panjaitan; Salmiah; Dewi Rahma Yanti; Dian Pebriyani (Universitas Muhammadiyah Malang, 2023)
Oil palm farmers is act as producer and price takers and their bargaining position is often unequal, and farmers are disadvantaged by the condition. A large number of intermediaries involved in the marketing process indicates long marketing channel. Long marketing channel of a product results in greater marketing costs; such circumstances would lead to inefficient marketing channel. This research is purposed to analyze marketing channel, marketing margin, famer’s share and marketing efficiency for oil palm in Pasar VII Namo Terasi Village. Result shows that there are 2 types of Marketing channels for Oil Palm in Pasar VIII Namo Terasi Village, Sei Bingai District, Langkat Regency which are Marketing Channel I (Farmers–Intermediaries–Oil Palm Factory) and Marketing Channel II (Farmers–Oil Palm Factory). Marketing Channel with the highest Farmer’s Share is Marketing Channel II, with the share of farmer’s value being about 100%. Either marketing channel 1 and marketing channel II are categorized as efficient.Result shows that marketing channel pattern II is the most efficient marketing channel.